Outcomes of percutaneous cholecystostomy and predictors of subsequent cholecystectomy. Issue 7 (20th October 2017) - Cooper, Scott; Donovan, Michael; Grieve, David A.
Abstract : Background: The use of a percutaneous cholecystostomy (PC) in the management of severe acute cholecystitis is a well recognized alternative to acute cholecystectomy. The need for definitive surgical management remains controversial. Methods: A retrospective analysis of hospital records at Nambour General Hospital between 2012 and 2016 was conducted and data relating to indications, demographics, comorbidities and outcomes were collected. Results: Thirty PC patients (20 male and 10 female) were identified, with a mean age of 77 years (range 46–93). Thirteen proceeded to cholecystectomy, nine elective and four emergent. Mean time to operation was 97 days (range 1–480). Ten were performed laparoscopically with a complication rate of 23% (3/13). One patient in the operative group died. Seventeen patients did not proceed to cholecystectomy. Fifteen resolved and were discharged, and two died. Three of those discharged were readmitted with gallstone disease requiring treatment, one of which died. A total of 71% (12/17) of the non‐operative group died and three of those had a cause of death related to gallstone disease. The operative group was younger ( P = 0.01) and had a lower estimated mortality risk ( P < 0.05). In this cohort, this translated to an overall survival benefit ( P < 0.01). Conclusion: Predictors of eventual cholecystectomy include younger age and lower estimated mortality risk. Patients who require a PC for the treatment of acute cholecystitis and subsequently go on to cholecystectomy can expect to have a favourable outcome.